The caring hand that cripples: The East Germany labour market after reunification - Dennis J. Snower; Christian Merkl (Centre for Economic Policy Research (CEPR), 2006)
The East German labour market has hardly made any progress since German reunification, despite massive migration flows and support from the West. We argue that East Germany is in trouble precisely because of the support it has received. This paper explores the phenomenon of 'the caring hand that cripples,' arising from bargaining by proxy, the adoption of the West German welfare system and the associated employment persistence. Even the steady decrease of labour cost (normalized by productivity) since the beginning of the 1990s did not help to kick start the East. We suggest that labour force participants fell into 'traps,' concerning low skills, ageing of the workforce, labour-saving capital and skills, capital underutilization, and unemployment arising from the decline of the tradeable sector.
Keywords: E24; J3; P2; 330; Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Sozialstaat; Wirtschaftliche Anpassung; Subvention; Neue Bundesländer